Textbooks Of Islamic Education For Secondary School In Malaysia And Somalia In The Topic Of Akhlak: A Comparative Study - Halim Bin Ismail; Siti Munirah Binti Rusli; Nur Shuhada Binti Shuib; Amiin Jirde Yusuf; Noor Azizi Ismail; Mohd Aderi Che Noh (Turkish Journal of Physiotherapy and Rehabilitation, 2024)
Volume: 32 - Issue: 3 (pages:19153-19162)